Irreparable massive rotator cuff tear in a young patient with recurrent anterior shoulder dislocation - Yeak, Raymond Dieu Kiat; Campbell, Peter T. (Universiti Putra Malaysia Press, 2020)
Combined latissimus dorsi transfer, subscapularis repair and Latarjet surgery is rare and has never been reported. A 35-year-old man with chronic shoulder pain had a long history of instability of his right shoulder. The first episode occurred during a game of touch rugby followed by multiple episodes of subluxation. MRI was done which showed complete tear of the subscapularis anteriorly which was retracted and atrophied indicating a longstanding tear. There was also significant mid substance supraspinatus tendon tear. Patient then underwent two surgeries. The initial surgery found the rotator cuff to be irreparable with glenoid bone loss and only acromioplasty with acromioclavicular joint resection were performed. He then had a single stage surgery consisting of latissimus dorsi transfer, Latarjet procedure and subscapularis repair. A two-stage surgery can be avoided, and good results can be obtained provided that the patient undergo correct rehabilitation regime after undergoing a single stage surgery.